2006
DOI: 10.1152/ajpregu.00588.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-2 acutely increases proximal small intestinal blood flow in TPN-fed neonatal piglets

Abstract: . Glucagon-like peptide-2 acutely increases proximal small intestinal blood flow in TPN-fed neonatal piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…However, it is unknown how rapidly these cell signaling events are activated or how quickly the TPN-induced mucosal atrophy is reversed after GLP-2 treatment in vivo. We hypothesized that GLP-2 infusion in TPN-fed piglets would lead to rapid activation of cell signaling based on evidence that intestinal blood flow is significantly increased within 15 min of infusion (14,40). Our results indicate that GLP-2 infusion rapidly (1-4 h) induced intestinal PKA phosphorylation and putative downstream signals associated with increased cell survival, including PKB/ GSK-3/Bcl-2.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it is unknown how rapidly these cell signaling events are activated or how quickly the TPN-induced mucosal atrophy is reversed after GLP-2 treatment in vivo. We hypothesized that GLP-2 infusion in TPN-fed piglets would lead to rapid activation of cell signaling based on evidence that intestinal blood flow is significantly increased within 15 min of infusion (14,40). Our results indicate that GLP-2 infusion rapidly (1-4 h) induced intestinal PKA phosphorylation and putative downstream signals associated with increased cell survival, including PKB/ GSK-3/Bcl-2.…”
Section: Discussionmentioning
confidence: 86%
“…However, despite the recent evidence from cell culture studies, there are no in vivo studies confirming whether GLP-2 activates intestinal ERK1/2 signaling and whether this is associated with changes in crypt cell proliferation. Thus the aim of the current study was to further establish the physiological relevance of these signaling pathways in vivo by quantifying their temporal activation in piglets treated with GLP-2 for 1, 4, and 48 h. We were especially interested in the early activation of these two apparently divergent pathways and their association with intestinal epithelial cell survival and proliferation because previous evidence showed that GLP-2 maximally increases small intestinal blood flow within 30 min after infusion in neonatal piglets (14,15,40). .…”
mentioning
confidence: 99%
“…The integrative GI responses to GLP-2 are mediated via the GLP-2 receptor, a member of the glucagon/secretin G protein-coupled receptor superfamily that is located on enteric (Bjerknes and Cheng, 2001) and vagal (Nelson et al, 2007) nerves, subepithelial myofibroblasts (Orskov et al, 2005), and a subset of intestinal epithelial cells . Activation of GLP-2 receptors regulates epithelial cell growth (Bjerknes and Cheng, 2001), reduces intestinal permeability (Estall and Drucker, 2006), increases mesenteric blood flow (Guan et al, 2006;Stephens et al, 2006), and promotes nutrient absorption (Nelson et al, 2007).…”
mentioning
confidence: 99%
“…GLP-2 analogs (Teduglutide, NPS Pharmaceuticals, Bedminster, NJ) have been the subject of clinical trials that have shown safety and efficacy in the promotion of intestinal growth in SBS patients (19,20). GLP-2 has subsequently been demonstrated to increase blood flow to the superior mesenteric artery (21)(22)(23) and portal vein (24). Increased blood flow is necessary during growth of the small bowel; however, the mechanism by which GLP-2 affects blood flow is unknown.…”
Section: Introductionmentioning
confidence: 99%